Fluid catalytic cracking using catalyst systems containing modified beta zeolite additives

JP7643815B2Active Publication Date: 2025-03-11SAUDI ARABIAN OIL CO +2
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023504548
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-05
Filing Date
2021-05-26
Publication Date
2025-03-11
Estimated Expiration
2041-05-26

AI Technical Summary

Benefits of technology

【0010】 本明細書に記載される実施形態のさらなる特徴及び利点は、以下の詳細な説明に記載されており、一部には、その説明から当業者には容易に明らかになり、あるいは、以下の詳細な説明、特許請求の範囲、並びに添付の図面を含む、本明細書に記載される実施形態を実施することによって認識される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643815000003
    Figure 0007643815000003
  • Figure 0007643815000004
    Figure 0007643815000004
  • Figure 0007643815000001
    Figure 0007643815000001
Patent Text Reader

Abstract

A method for cracking a hydrocarbon oil includes contacting the hydrocarbon oil with a catalyst system in a fluid catalytic cracking unit to produce light olefins and gasoline fuel. The catalyst system includes an FCC-based catalyst and a catalyst additive. The FCC-based catalyst includes a Y-zeolite. The catalyst additive includes a framework-substituted Y-zeolite. * Includes BEA-type zeolites. * BEA-type zeolites are modified * It has a BEA backbone. Modified * The BEA skeleton is * modified by substituting a portion of the framework aluminum atoms of the BEA aluminosilicate framework with beta zeolite Al-substituting atoms selected from titanium, zirconium, hafnium, and combinations thereof; * The FCC-based catalyst may contain a framework-substituted ultrastable Y (USY)-zeolite as the Y-zeolite. The framework-substituted USY-zeolite has a USY aluminosilicate framework modified by substituting a portion of the framework aluminum atoms with titanium, zirconium, hafnium, or a combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS

[0001] This application claims priority to U.S. Patent Application No. 16 / 985,588, filed August 5, 2020, the entire disclosure of which is incorporated herein by reference. [Technical field]

[0002] This application relates to a process for fluid catalytic cracking of hydrocarbons, and more particularly to a process for fluid catalytic cracking of a hydrocarbon feed using a catalyst system comprising a zeolite catalyst and a zeolite catalyst additive. [Background technology]

[0003] In the fluid catalytic cracking (FCC) process, petroleum-derived hydrocarbons are catalytically cracked using an acidic catalyst maintained in a fluidized state where the acidic catalyst is continuously regenerated. The primary product from such processes is generally gasoline. Other products such as liquid petroleum gas and cracked gas oil are also produced in small amounts via the FCC process. Coke that accumulates on the catalyst is burned off at high temperatures in the presence of air before the regenerated catalyst is returned to the reaction zone for recycling.

[0004] Fluid catalytic cracking is the largest refining process used to produce gasoline, with a global production capacity of 14.2 million barrels per day (approximately 226 million barrels per day). 3 ). The process converts heavy feedstocks such as vacuum distillates, atmospheric resids, and deasphalted oils into lighter products that are rich in olefins and aromatics. FCC catalyst systems typically contain finely divided solid acids such as zeolites, aluminum silicates, treated clays (kaolin), bauxite, and silica-alumina.

[0005] Additives can be included in the FCC catalyst system to significantly improve the octane number of the gasoline fraction or the yield of light olefins such as propylene. The global demand for propylene is continuously increasing. Nearly 60% of the total propylene is produced by steam cracking of various hydrocarbon streams such as naphtha, diesel, and liquefied petroleum gas (LPG). More than 30% of the propylene produced worldwide is obtained from the FCC process. Summary of the Invention [Problem to be solved by the invention]

[0006] Thus, there is a continuing need for catalyst systems that increase the yield of propylene in general, as well as catalyst additives that increase the propylene yield in otherwise known catalyst systems. [Means for solving the problem]

[0007] Against the foregoing background, an exemplary embodiment of the present disclosure is directed to a method for cracking a hydrocarbon oil. The method includes contacting the hydrocarbon oil with a catalyst system in a fluid catalytic cracking unit to produce light olefins and gasoline fuel. The catalyst system includes an FCC-based catalyst and a catalyst additive. The FCC-based catalyst includes a Y-zeolite. The catalyst additive includes a framework-substituted Y-zeolite. * Includes BEA-type zeolites. Framework-substituted * BEA-type zeolites are modified * It has a BEA backbone. Modified * The BEA skeleton is * The BEA aluminosilicate framework has been modified by replacing a portion of the framework aluminum atoms with beta zeolite Al-substituting atoms independently selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof. * It can be a BEA aluminosilicate framework.

[0008] According to some embodiments, the Y-zeolite of the FCC-based catalyst may be a framework-substituted ultrastable Y (USY) zeolite. In such embodiments, the framework-substituted USY-zeolite has a modified USY framework. The modified USY framework may be a USY aluminosilicate framework that has been modified by replacing a portion of the framework aluminum atoms of the USY aluminosilicate framework with USY-zeolite Al-substituting atoms independently selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof.

[0009] These and other features, aspects, and advantages of the present invention will become better understood with reference to the following description and appended claims.

[0010] Additional features and advantages of the embodiments described herein are set forth in the detailed description which follows, and in part will be readily apparent to those skilled in the art from that description, or may be learned by practicing the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings.

[0011] It should be understood that both the foregoing general description and the following detailed description describe various embodiments and are intended to provide an overview or framework for understanding the nature and character of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments, and are incorporated in and constitute a part of this specification. The drawings illustrate various embodiments described herein and, together with the description, serve to explain the principles and operation of the claimed subject matter. [Brief description of the drawings]

[0012] [Figure 1] Schematic diagram of a riser fluid catalytic cracking unit [Diagram 2] Schematic diagram of a downflow fluid catalytic cracking unit DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Reference will now be made in detail to an embodiment of a method for cracking a hydrocarbon oil, the method including contacting the hydrocarbon oil with a catalyst system in a fluid catalytic cracking unit to produce light olefins and gasoline fuel. The catalyst system includes at least an FCC-based catalyst and a catalyst additive. The FCC-based catalyst includes a Y-zeolite.

[0014] Skeleton replaced * The catalyst system of the embodiment comprising the BEA-type zeolite catalyst additive and its preparation will now be described in detail, and its incorporation in a process for fluid catalytic cracking of hydrocarbons will be described later.

[0015] FCC-based catalysts In an embodiment of the method for cracking a hydrocarbon oil, the catalyst system with which the hydrocarbon oil is contacted comprises an FCC-based catalyst. The FCC-based catalyst can be any zeolite catalyst known to be suitable for use in fluid catalytic cracking processes. Suitable FCC-based cracking catalysts have a bulk density of 0.5 g / mL to 1.0 g / mL, an average particle size of 50 μm to 90 μm, a molecular weight of 50 μm to 100 μm, and a molecular weight of 50 μm to 100 μm. 2 / g to 350m 2 / g and a pore volume of 0.05 mL / g to 0.5 mL / g.

[0016] In an embodiment, the FCC-based catalyst is or comprises a Y-zeolite. In some embodiments, the Y-zeolite can be an ultrastable Y (USY) zeolite. In some embodiments, the Y-zeolite can be a modified USY-zeolite, such as a framework-substituted USY-type zeolite. The FCC-based catalyst comprising framework-substituted USY-type zeolite has high cracking activity, which is effective for producing light olefins and gasoline, with low dry gas and coke production. Framework-substituted USY-type zeolite is described in detail below.

[0017] The framework-substituted ultrastable Y (USY) type zeolite according to the embodiment has a modified USY framework. The modified USY framework is similar to a USY aluminosilicate framework according to the standard definition of a USY aluminosilicate framework. According to the standard definition, a USY aluminosilicate framework has a crystal lattice parameter (UD) of 2.430 nm or more and 2.460 nm or less, a lattice constant (UD) of 600 nm or more, and a lattice constant (UD) of 600 nm or more. 2 / g to 900m 2 / g and a silicon to aluminum molar ratio of 5 to 100, calculated on a silica (SiO2) and alumina (Al2O3) basis.

[0018] With respect to framework-substituted USY-type zeolites according to embodiments of the present disclosure, the modified USY framework is a USY aluminosilicate framework that has been modified by replacing a portion of the framework aluminum atoms of the USY aluminosilicate framework with USY-zeolite Al-substituting atoms, in embodiments, the USY-zeolite Al-substituting atoms are independently selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof.

[0019] As used in this disclosure, the term "Ti-USY" refers to framework-substituted USY-type zeolites according to embodiments where the substituted atoms are titanium. Similarly, the term "Zr-USY" refers to framework-substituted USY-type zeolites according to embodiments where the USY-zeolite Al-substituted atoms include zirconium. The term "Hf-USY" refers to framework-substituted USY-type zeolites according to embodiments where the USY-zeolite Al-substituted atoms include hafnium. The term "(Ti,Zr)-USY" refers to framework-substituted USY-type zeolites according to embodiments where the USY-zeolite Al-substituted atoms include titanium and zirconium. The term "(Ti,Hf)-USY" refers to framework-substituted USY-type zeolites according to embodiments where the USY-zeolite Al-substituted atoms include titanium and hafnium. The term "(Zr,Hf)-USY" refers to framework-substituted USY-type zeolites according to embodiments where the USY-zeolite Al-substituted atoms include zirconium and hafnium. The term "(Ti,Zr,Hf)-USY" refers to a framework-substituted USY-type zeolite according to an embodiment, where the USY-zeolite Al-substituted atoms include titanium, zirconium, and hafnium.

[0020] The framework-substituted USY-type zeolite according to the embodiment can be Ti-USY, Zr-USY, Hf-USY, (Ti,Zr)-USY, (Ti,Hf)-USY, (Zr,Hf)-USY, or (Ti,Zr,Hf)-USY as previously defined. The USY-zeolite Al-substituted atoms replace the aluminum atoms that form the framework of the ultrastable Y-type zeolite, and thus function as framework building blocks of the ultrastable Y-type zeolite. The substitution can be verified by analytical techniques, including but not limited to ultraviolet, visible, and near-infrared spectroscopy (UV-Vis-NIR), Fourier transform infrared spectroscopy (FT-IR), or nuclear magnetic resonance spectroscopy (NMR).

[0021] In some embodiments, the framework-substituted USY-type zeolite contains 0.01% to 5%, or 0.1% to 5%, or 0.2% to 4%, or 0.3% to 3% by weight of USY-zeolite Al-substituted atoms, calculated on an oxide basis, based on the total weight of the framework-substituted USY-type zeolite. In the oxide basis calculations, titanium atoms are calculated on a TiO2 basis, zirconium atoms are calculated on a ZrO2 basis, and hafnium atoms are calculated on a HfO2 basis. Titanium, zirconium, and hafnium in the framework-substituted USY-type zeolite can be quantitatively determined by known techniques, such as, for example, X-ray fluorescence analysis, high frequency plasma emission spectrometry, or atomic absorption spectrometry.

[0022] In some embodiments, in addition to the substitution atoms substituted on the aluminum framework, the framework-substituted USY-type zeolite may further include zirconium atoms, titanium atoms, hafnium atoms, or any combination thereof, attached to the framework of the framework-substituted USY-type zeolite or supported on the outside of the framework or combined with the framework. In such embodiments, the zirconium, titanium, or hafnium atoms may be attached as oxide particles, such as titania particles, zirconia particles, or hafnia particles. The oxide particles may have a particle size of 50 nm or less. For the purposes of facilitating quantitative analysis, as contemplated herein, the amount by mass of substitution atoms in the framework-substituted USY-type zeolite is calculated on an oxide basis and includes the total amount of titanium, zirconium, and hafnium, based on the total mass of the framework-substituted USY-type zeolite, which replaces framework aluminum atoms or is attached to, supported on the outside of, or combined with the zeolite framework. However, in all embodiments, it is understood that at least a portion of the framework aluminum atoms of the USY aluminosilicate framework are substituted with titanium, zirconium, hafnium atoms, or any combination thereof. In exemplary embodiments, more than 50%, or more than 75%, or more than 90%, or more than 99% of the titanium, zirconium, and hafnium atoms present in the framework-substituted USY-type zeolite substitute for framework aluminum atoms in the zeolite framework, and are not merely attached to or supported on the outside of or associated with the zeolite framework, particularly as particles.

[0023] Those skilled in the art should recognize that when the framework-substituted USY-type zeolite contains a combination of USY-zeolite Al-substituted atoms, such as (Ti,Zr)-USY, (Ti,Hf)-USY, (Zr,Hf)-USY, or (Ti,Zr,Hf)-USY, the mass ratio of the individual types of USY-zeolite Al-substituted atoms in each zeolite calculated on an oxide basis is not limited. The reaction described in the method according to the embodiment can be adjusted by adjusting the ratio of titanium to zirconium to hafnium, but it should be understood that the ratio of titanium to zirconium to hafnium can be effective in carrying out the method for cracking hydrocarbon oil according to the present disclosure.

[0024] The framework-substituted USY-type zeolite in the catalyst system can be prepared by any zeolite preparation method that results in a framework-substituted USY-type zeolite having a USY aluminosilicate framework in which a portion of the framework aluminum atoms are replaced with titanium atoms, zirconium atoms, hafnium atoms, or any combination thereof. In one example of a preparation technique, the framework-substituted USY-type zeolite in the catalyst system has a crystal lattice constant of 2.430 nm to 2.460 nm, a crystal lattice constant of 600 m 2 / g to 900m 2 A USY type zeolite having a specific surface area of ​​1000 / g and a silica to alumina molar ratio of 5 to 100 can be produced by calcination at 500°C to 700°C. A suspension containing the calcined USY type zeolite is then formed. The suspension can have a liquid / solid mass ratio of 5 to 15. An inorganic or organic acid is added to the suspension to lower the pH of the suspension to less than 2.0. The pH of the suspension is controlled beforehand to less than 2.0 to prevent precipitation during the mixing of the one or more additional solutions. Specifically, one or more additional solutions containing compounds of zirconium, titanium, hafnium, or combinations thereof are mixed into the suspension to cause framework substitution at aluminum sites. The suspension is then neutralized with a base, such as, for example, aqueous ammonia, to raise the pH to, for example, a range of 7 to 7.5. The resulting framework-substituted USY type zeolite can be filtered, washed with water, and dried at a drying temperature of, for example, 80°C to 180°C.

[0025] In preparing the framework-substituted USY-type zeolite, the ultrastable Y-type zeolite raw material can be calcined at 500°C to 700°C, or 550°C to 650°C. The calcination time is not particularly limited as long as the framework-substituted USY-type zeolite is obtained. An exemplary calcination time can be 30 minutes to 10 hours. As for the calcination atmosphere of the USY-type zeolite raw material, the calcination is preferably carried out in air. The calcined USY-type zeolite raw material is suspended in water having a temperature of 20°C to 30°C to form a suspension. As for the concentration of the suspension of the USY-type zeolite, the liquid / solid mass ratio can be, for example, 5 to 15, or 8 to 12.

[0026] Non-limiting examples of inorganic acids for lowering the pH of the suspension in the preparation of framework-substituted USY-type zeolite may include sulfuric acid, nitric acid, or hydrochloric acid. Examples of organic acids for lowering the pH of the suspension in the preparation of framework-substituted USY-type zeolite may include carboxylic acids. The amount of inorganic or organic acid is not limited as long as the pH of the suspension can be controlled in a range of less than 2.0. Non-limiting examples of the amount of acid include 0.5 to 4.0 times, or 0.7 to 3.5 times the molar amount of alumina in the framework-substituted USY-type zeolite.

[0027] Non-limiting examples of titanium compounds present in the additional solution mixed into the suspension during preparation of the framework-substituted USY-type zeolite include titanium sulfate, titanium acetate, titanium chloride, titanium nitrate, titanium lactate, and any titanium compound having sufficient solubility in the suspension to allow the titanium atoms to substitute for the aluminum atoms in the zeolite framework. In an embodiment, an aqueous solution of a titanium compound prepared by dissolving a titanium compound in water is preferably used as the titanium compound.

[0028] Non-limiting examples of zirconium compounds present in the additional solution mixed into the suspension during preparation of the framework-substituted USY-type zeolite include zirconium sulfate, zirconium nitrate, zirconium chloride, and any zirconium compound having sufficient solubility in the suspension for the zirconium atoms to substitute for the aluminum atoms in the zeolite framework. In an embodiment, an aqueous solution of a zirconium compound prepared by dissolving a zirconium compound in water is preferably used as the zirconium compound.

[0029] Non-limiting examples of hafnium compounds present in the additional solution mixed into the suspension during preparation of the framework-substituted USY-type zeolite include hafnium chloride, hafnium nitrate, hafnium fluoride, hafnium bromide, hafnium oxalate, and any hafnium compound having sufficient solubility in the suspension for the hafnium atoms to substitute for the aluminum atoms in the zeolite framework. In an embodiment, an aqueous solution of a hafnium compound prepared by dissolving a hafnium compound in water is preferably used as the hafnium compound.

[0030] In the preparation of framework-substituted USY-type zeolite, when an aqueous solution of a zirconium compound, a hafnium compound, or a titanium compound is mixed with a suspension of ultrastable Y-type zeolite, the aqueous solution may be gradually added to the suspension. After the addition of the aqueous solution to the suspension is completed, the solution can be mixed by stirring for example at room temperature (25°C ± 10°C) for 3 to 5 hours. Furthermore, after the mixing is completed, the above-mentioned mixed solution can be neutralized by adding an alkali such as ammonia water, and the pH can be controlled to 7.0 to 7.5, thereby obtaining framework-substituted zeolite in the catalyst.

[0031] Catalyst Additives In an embodiment of the method for cracking a hydrocarbon oil, in addition to the FCC-based catalyst, the catalyst system with which the hydrocarbon oil is contacted includes a catalyst additive. The catalyst additive is a backbone-substituted * Includes BEA-type zeolites. Framework-substituted * BEA-type zeolites are modified* It has a BEA skeleton.

[0032] Modified * The BEA skeleton is * According to the standard definition of the BEA aluminosilicate framework * It is similar to the BEA aluminosilicate framework. According to the standard definition: * The BEA aluminosilicate framework has crystal lattice constants a and b (UD) of 1.260 nm to 1.270 nm, a unit cell length c of 2.62 nm to 2.65 nm, and a 2 / g to 800m 2 / g and a silicon to aluminum molar ratio of 10 to 200, calculated on a silica (SiO2) and alumina (Al2O3) basis.

[0033] Backbone-substituted according to embodiments of the present disclosure * For BEA-type zeolites, modified * The BEA aluminosilicate framework is * modified by replacing a portion of the framework aluminum atoms of the BEA aluminosilicate framework with beta zeolite Al-replacement atoms independently selected from the group consisting of titanium atoms, zirconium atoms, and hafnium atoms, and combinations thereof; * BEA aluminosilicate framework.

[0034] As used in this disclosure, "Ti- * The term "BEA" refers to a backbone substituted cation in accordance with an embodiment, where the substituted atom is titanium. * It refers to BEA type zeolite. * The term "BEA" refers to a beta zeolite framework substituted zeolite according to an embodiment, in which the Al-substituted atoms include zirconium. * Refers to BEA type zeolite. * The term "BEA" refers to a beta zeolite framework substituted zeolite according to an embodiment, in which the Al-substituted atoms include hafnium. * This refers to BEA type zeolite. (Ti,Zr)- *The term "BEA" refers to a beta zeolite framework substituted Al-substituted atom, according to an embodiment, which includes titanium and zirconium. * This refers to BEA type zeolite. (Ti,Hf)- * The term "BEA" refers to a beta zeolite framework substituted Al-substituted atom according to an embodiment, which includes titanium and hafnium. * Refers to BEA type zeolite. (Zr,Hf)- * The term "BEA" refers to a beta zeolite framework substituted Al-substituted atom according to an embodiment, which includes zirconium and hafnium. * Refers to BEA type zeolite. (Ti,Zr,Hf)- * The term "BEA" refers to a beta zeolite framework substituted zeolite according to an embodiment, where the Al-substituted atoms include titanium, zirconium, and hafnium. * This refers to BEA type zeolite.

[0035] The framework-substituted *BEA type zeolites according to the embodiment are Ti- * BEA, Zr- * BEA, Hf- * BEA, (Ti, Zr)- * BEA, (Ti,Hf)- * BEA, (Zr,Hf)- * BEA, or (Ti, Zr, Hf)- * Beta zeolite Al substitution atoms can be: * Substitutes aluminum atoms that form the framework of BEA-type zeolites, and therefore * It functions as a structural component of the BEA-type zeolite framework. The substitution can be verified by analytical techniques including, but not limited to, ultraviolet, visible, and near-infrared spectroscopy (UV-Vis-NIR), Fourier transform infrared spectroscopy (FT-IR), or nuclear magnetic resonance spectroscopy (NMR).

[0036] In some embodiments, the backbone substituted * BEA-type zeolites are framework-substituted *Beta zeolite contains 0.01% to 5%, or 0.1% to 5%, or 0.2% to 4%, or 0.3% to 3%, by weight, of Al-substituted atoms, calculated on an oxide basis, based on the total weight of the BEA-type zeolite. In the oxide basis calculations, titanium atoms are calculated on a TiO2 basis, zirconium atoms are calculated on a ZrO2 basis, and hafnium atoms are calculated on a HfO2 basis. Framework-substituted * Titanium, zirconium and hafnium in BEA type zeolites can be quantitatively determined by known techniques such as, for example, X-ray fluorescence spectrometry, radio frequency plasma emission spectrometry or atomic absorption spectrometry.

[0037] In some embodiments, in addition to the aluminum framework substituted beta zeolite Al-substituted atoms, framework substituted * BEA-type zeolites are framework-substituted * The BEA-type zeolite may further include zirconium, titanium, hafnium atoms, or any combination thereof, attached to or supported on the outside of or associated with the framework of the zeolite. In such embodiments, the zirconium, titanium, or hafnium atoms may be attached as oxide particles, such as titania, zirconia, or hafnia particles. The oxide particles may have a particle size of 50 nm or less. For purposes of facilitating quantitative analysis, as contemplated herein, framework substituted ions may be used. * The amount by weight of substitution atoms in BEA-type zeolites is calculated on an oxide basis and includes framework substituted atoms which either replace framework aluminum atoms or are attached to or supported on the outside of the zeolite framework or are combined therewith. * The total amount of titanium, zirconium, and hafnium is based on the total weight of the BEA type zeolite. However, in all embodiments, * It is understood that at least a portion of the framework aluminum atoms of the BEA aluminosilicate framework are substituted with titanium atoms, zirconium atoms, hafnium atoms, or any combination thereof. In an exemplary embodiment, the framework is substituted *More than 50%, or more than 75%, or more than 90%, or more than 99% of the titanium, zirconium, and hafnium atoms present in BEA type zeolites substitute for framework aluminum atoms in the zeolitic framework and are not only bound to or supported on the outside of or associated with the zeolitic framework, particularly as particles.

[0038] Those skilled in the art will recognize that backbone substituted * BEA type zeolites are (Ti,Zr)- * BEA, (Ti,Hf)- * BEA, (Zr,Hf)- * BEA, or (Ti, Zr, Hf)- * It should be appreciated that when a beta zeolite contains a combination of Al-substituted atoms, such as BEA, the mass ratio of the individual types of beta zeolite Al-substituted atoms in each zeolite, calculated on an oxide basis, is not limited. It should be understood that the reaction described in the method according to the embodiment can be adjusted by adjusting the ratio of titanium to zirconium to hafnium, but any ratio of titanium to zirconium to hafnium can be effective in carrying out the method for cracking hydrocarbon oil according to the present disclosure.

[0039] Backbone-substituted catalyst systems * BEA-type zeolites are those in which some of the framework aluminum atoms are replaced with titanium atoms, zirconium atoms, hafnium atoms, or any combination thereof. * Framework-substituted BEA aluminosilicate framework * The catalyst system can be prepared by any zeolite preparation method that results in a BEA type zeolite. In one example of a preparation technique, the framework substituted * BEA-type zeolites have crystal lattice constants a and b of 1.260 nm to 1.270 nm, unit cell length c of 2.62 nm to 2.65 nm, and 2 / g to 800m 2 / g and a silica to alumina molar ratio of 10 to 200, or 10 to 100, or 30 to 70. *It can be produced by calcining BEA-type zeolite at 500 to 700 °C. * A suspension containing BEA type zeolite is formed. The suspension may have a liquid / solid mass ratio of 5 to 15 based on the liquids and solids present in the suspension. An inorganic or organic acid is added to the suspension to lower the pH of the suspension to less than 2.0. The pH of the suspension is controlled beforehand to less than 2.0 to prevent precipitation during mixing of the one or more additional solutions. Specifically, one or more additional solutions containing compounds of zirconium, titanium, hafnium, or combinations thereof are mixed into the suspension to cause framework substitution at the aluminum sites. The suspension is then neutralized with a base, such as, for example, aqueous ammonia, to raise the pH to, for example, a range of 7 to 7.5. The resulting framework-substituted zeolite is then dissolved in water. * The BEA type zeolite can be filtered, washed with water and dried at a drying temperature of, for example, 80°C to 180°C.

[0040] (Ti,Zr)- by embodiment * BEA backbone substituted * One specific, non-limiting preparation of a BEA-type zeolite has a silica to alumina ratio of 28.5. * 51.4 g of the zeolite with the BEA framework are suspended in 450 g of deionized water and heated to 40° C. Then, 14.8 g of H2SO4 (25% by weight) are added together with 10.0 g of an aqueous solution of titanium sulfate (corresponding to 5% by weight of TiO2) prepared by adding 1.52 g of titanium sulfate to 8.48 g of deionized water (corresponding to 33% by weight of TiO2 in the aqueous solution). To this solution is added an additional aqueous solution of zirconium sulfate (2.8 g, constituting 18% by weight of ZrO2). The mixture is stirred at 60° C. for 4 hours, then filtered and washed with 1.5 liters of deionized water. The resulting zeolite is dried at 110° C. to obtain the framework-substituted zeolite (Ti,Zr)- * Get BEA.

[0041] Skeleton replaced * In the preparation of BEA type zeolites, an aqueous solution of a zirconium compound, a hafnium compound, or a titanium compound is added.* When mixing with a suspension of BEA-type zeolite, the aqueous solution may be added gradually to the suspension. After the addition of the aqueous solution to the suspension is completed, the solution may be mixed, for example, by stirring at room temperature (25°C ± 10°C) for 3 to 5 hours. Furthermore, after the mixing is completed, the above mixed solution may be neutralized by adding an alkali such as ammonia water, and the pH may be controlled to 7.0 to 7.5, thereby obtaining a framework-substituted zeolite in the catalyst.

[0042] Skeleton replaced * In the preparation of BEA type zeolites, * The BEA type zeolite raw material can be calcined at 500° C. to 700° C. or 550° C. to 650° C. The calcination time depends on the framework substituted. * There is no particular limitation as long as a BEA type zeolite is obtained. Exemplary calcination times can be from 30 minutes to 10 hours. * As regards the calcination atmosphere of the BEA type zeolite raw material, it is preferably carried out in air. * The BEA type zeolite raw material is suspended in water having a temperature of 20° C. to 30° C. to form a suspension. * With regard to the concentration of the suspension of zeolite of the BEA type, the liquid / solid mass ratio may be, for example, from 5 to 15, or from 8 to 12.

[0043] Skeleton replaced * Non-limiting examples of inorganic acids for lowering the pH of the suspension in the preparation of BEA-type zeolites may include sulfuric acid, nitric acid, or hydrochloric acid. * Examples of organic acids for lowering the pH of the suspension in the preparation of BEA-type zeolites may include carboxylic acids. The amount of inorganic or organic acid is not limited as long as it can control the pH of the suspension to a range of less than 2.0. Non-limiting examples of the amount of acid include framework-substituted * The acid is included in an amount from 0.5 to 4.0 times, or from 0.7 to 3.5 times, the molar amount of alumina in the BEA type zeolite.

[0044] Skeleton replaced *Non-limiting examples of titanium compounds present in the additional solution mixed into the suspension during the preparation of the BEA type zeolite include titanium sulfate, titanium acetate, titanium chloride, titanium nitrate, titanium lactate, and any titanium compound having sufficient solubility in the suspension to allow the titanium atoms to replace the aluminum atoms in the zeolite framework. In an embodiment, an aqueous solution of a titanium compound prepared by dissolving a titanium compound in water is preferably used as the titanium compound.

[0045] Skeleton replaced * Non-limiting examples of zirconium compounds present in the additional solution mixed into the suspension during the preparation of the BEA type zeolite include zirconium sulfate, zirconium nitrate, zirconium chloride, and any zirconium compound having sufficient solubility in the suspension to allow the zirconium atoms to replace the aluminum atoms in the zeolite framework. In an embodiment, an aqueous solution of a zirconium compound prepared by dissolving a zirconium compound in water is preferably used as the zirconium compound.

[0046] Skeleton replaced * Non-limiting examples of hafnium compounds present in the additional solution mixed into the suspension during the preparation of the BEA type zeolite include hafnium chloride, hafnium nitrate, hafnium fluoride, hafnium bromide, hafnium oxalate, and any hafnium compound having sufficient solubility in the suspension to allow the hafnium atoms to replace the aluminum atoms in the zeolite framework. In an embodiment, an aqueous solution of a hafnium compound prepared by dissolving a hafnium compound in water is preferably used as the hafnium compound.

[0047] According to an embodiment, the backbone-substituted * The BEA-type zeolite catalyst additive is (a) 400 m 2 / g to 800m 2 / g; (b) SiO2 to Al2O3 molar ratio from 10 to 200; (c) 0.2 cm 3 / g to 0.6cm 3 / g pore volume; and (d) crystal lattice constants a = 1.26 nm to 1.27 nm, b = 1.26 nm to 1.27 nm, and c = 2.62 to 2.65 nm. * The catalyst additive containing a BEA-type zeolite may have a volume of pores with diameters of 600 angstroms or less (60 nm or less) of 0.40 mL / g to 0.75 mL / g. In a non-limiting example embodiment, the framework-substituted *BEA-type zeolite catalyst additive has (a) a pore volume of 400 m 2 / g to 800m 2 / g; (b) SiO2 to Al2O3 molar ratio of about 60; (c) 0.38 cm 3 / g to 0.43cm 3 / g; and (d) a (Ti,Zr)- with crystal lattice constants of a = 1.26 nm to 1.27 nm, b = 1.26 nm to 1.27 nm, and c = 2.62 to 2.65 nm. * It may include BEA zeolite. * The BEA type zeolite catalyst additive may have mesopores with diameters between 2 nm and 100 nm.

[0048] According to an embodiment of the method for cracking hydrocarbon oils, the catalyst system may include an FCC-based catalyst and a catalyst additive in a weight ratio of FCC-based catalyst to catalyst additive of from 2:1 to 1000:1, or from 2:1 to 100:1, or from 4:1 to 100:1, or from 6:1 to 20:1, or about 9:1, based on the combined weight of the FCC-based catalyst and the catalyst additive.

[0049] In a non-limiting example embodiment of the method for cracking a hydrocarbon oil, the catalyst additive is a backbone-substituted * Based on the total mass of the BEA type zeolite, calculated on an oxide basis, 0.01% to 5% of beta zeolite Al-substituted atoms (Ti,Zr)- * BEA backbone substituted *beta zeolite of the BEA type; beta zeolite Al-substituted atoms include titanium and zirconium atoms; FCC-based catalyst is a (Ti,Zr)-USY framework-substituted ultrastable Y-zeolite containing 0.01% to 5% USY-zeolite Al-substituted atoms, calculated on an oxide basis, based on the total mass of the framework-substituted ultrastable Y-zeolite; and USY-zeolite Al-substituted atoms include titanium and zirconium atoms.

[0050] Optional Components of the Catalyst System In embodiments of the method for cracking hydrocarbon oils, in addition to the FCC-based catalyst and catalyst additive, the catalyst system with which the hydrocarbon oil is contacted may optionally include one or more of a catalyst matrix support, a binder, a filler, and an active metal component.

[0051] The catalyst system of the method according to the embodiment comprises an FCC-based catalyst and a backbone-substituted * The support may include a support for the BEA-type zeolite catalyst additive. In some embodiments, the support is a support for the FCC-based catalyst and the framework-substituted * The inorganic oxide may include, except for one or both of the BEA-type zeolite catalyst additives. The inorganic oxide of the support may include a material that functions as a granulating agent or binder. Any material that is included in any known zeolite catalyst matrix support, including as a granulating agent, may be used. Examples of such inorganic oxides include, but are not limited to, alumina, silica, titania, silica-alumina, alumina-titania, alumina-zirconia, alumina-boria, phosphorus-alumina, silica-alumina-boria, phosphorus-alumina-boria, phosphorus-alumina-silica, silica-alumina-titania, and silica-alumina-zirconia. In an exemplary embodiment, the catalyst system includes, as the support, an inorganic oxide selected from alumina and silica-alumina. The silica-alumina support may be amorphous.

[0052] In embodiments where the catalyst system includes a catalyst matrix carrier, the weight ratio of zeolite to the catalyst matrix carrier may be varied according to the desired level of catalytic activity. In an exemplary embodiment, the mass of the catalyst matrix carrier in the catalyst system is determined relative to the mass of the zeolite in the catalyst system, regardless of the other components of the catalyst system. In an exemplary embodiment, the catalyst system may include from 10 wt% to 80 wt%, from 20 wt% to 70 wt%, or from 25 wt% to about 65 wt% zeolite, based on the total mass of all zeolites in the catalyst system. Similarly, the catalyst system may include a catalyst matrix carrier that constitutes from 20 wt% to 90 wt%, or from 30 wt% to 80 wt%, or from 35 wt% to 75 wt% of the catalyst system, based on the total mass of the catalyst system.

[0053] In a further exemplary embodiment, the catalyst system may include a binder such as a silica-based binder or an alumina-based binder. Silica-based binders and alumina-based binders can be used as inorganic binders. The silica-based binder can be any one or more of silica sol, water glass (sodium silicate), and silicic acid solution. For example, a silica sol containing SiO2 at a concentration in the range of 10 wt% to 15 wt% can be prepared by simultaneously and continuously adding water glass containing SiO2 at a concentration in the range of 12 wt% to 23 wt% and sulfuric acid having a concentration in the range of 20 wt% to 30 wt%. The aluminum compound binder can be (a) basic aluminum chloride, (b) aluminum metaphosphate, or (c) alumina sol. A solution obtained by dissolving any one or more of microcrystalline aluminas such as gibbsite, boehmite, and bayerite in an acid solution can be used as the aluminum-compound binder. Here, basic aluminum chloride is represented by [Al2(OH) n Cl 6-n m where n is an integer and m is a natural number, where 0 < n < 6 and 1 < m < 10, or in some embodiments, 4.8 < n < 5.3 and 3 < m < 7.

[0054] ​The catalyst system of the method according to the embodiment may further comprise an active metal component selected from an individual metal or combination of metals from IUPAC Groups 7 to 11 of the periodic table. Examples of active metals include iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, and tungsten. Non-limiting examples of combinations of metal components include molybdenum and tungsten; cobalt and nickel; and any one or more of molybdenum, tungsten, cobalt, or nickel in combination with a platinum group metal, such as platinum, rhodium, or palladium. In an exemplary embodiment, the catalyst system may comprise at least one active phase metal selected from nickel, molybdenum, tungsten, platinum, palladium, and combinations thereof. Without intending to be bound by theory, it is believed that framework substitution of aluminum with titanium, zirconium, or hafnium in framework-substituted USY-type zeolites according to embodiments can promote greater amounts of active metal distribution on the surface of the zeolite catalyst.

[0055] When an active metal component is included in the catalyst system, the catalyst system may comprise from greater than 0 to about 40% by weight of the metal component, calculated on an oxide basis for oxide components or on a metal basis for metals, based on the total mass of the catalyst system. In an exemplary embodiment, the catalyst system may comprise from 3% to 30% by weight of a metal component, such as iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, or tungsten, calculated on an oxide basis, based on the total mass of the catalyst system. In a further exemplary embodiment, the catalyst system may comprise from 0.01% to 2% by weight of a metal component selected from platinum, rhodium, or palladium, calculated on a metal basis, based on the total mass of the catalyst system.

[0056] The catalyst system of the method according to the embodiment comprises an FCC-based catalyst and a backbone-substituted *In addition to the BEA type zeolite catalyst additive, the catalyst may further include an additional FCC catalyst as an additive. Examples of such additional FCC catalysts include shape-selective zeolites that have a pore diameter smaller than that of Y type zeolites, and are therefore selective to allow hydrocarbons with only limited shapes to enter the zeolite through its pores. Examples of suitable shape-selective zeolite components include, for example, ZSM-5 zeolite, zeolite omega, SAPO-5 zeolite, SAPO-11 zeolite, SAPO-34 zeolite, and pentasil type aluminosilicate. When present in the catalyst system, the content of the additional shape-selective zeolite in the catalyst system may be about 0.01 wt% to 30 wt%, or about 0.01 wt% to 20 wt%, based on the total weight of the catalyst system.

[0057] In a non-limiting example embodiment, in a method for cracking a hydrocarbon oil, the catalyst system may include an FCC-based catalyst, a catalyst additive, a catalyst matrix support, a binder, and a filler. In such an example embodiment, the catalyst matrix support may include alumina or silica-alumina; the binder may be a sol of a porous inorganic oxide selected from the group consisting of alumina, silica, boria, chromia, magnesia, zirconia, titania, silica-alumina, and combinations thereof; the filler may be a clay selected from the group consisting of kaolin, montmorillonite, halloysite, bentonite, and combinations thereof. In a non-limiting example, the catalyst system may include 1% to 50% by mass of the FCC-based catalyst; 1% to 50% by weight of the catalyst additive; 0.1% to 15% by weight of the binder; and 0.1% to 15% by weight of the clay, based on the total weight of the catalyst system. In a further non-limiting example, the catalyst system can include, based on the total weight of the catalyst system, 1 wt. % to 50 wt. % FCC-based catalyst; 1 wt. % to 50 wt. % catalytic additive; 0.1 wt. % to 15 wt. % binder; and 0.1 wt. % to 15 wt. % clay, and the weight ratio of FCC-based catalyst to catalytic additive in the catalyst system can be 6:1 to 20:1, based on the combined weight of the FCC-based catalyst and catalytic additive.

[0058] Fluid Catalytic Cracking Process In a process for cracking a hydrocarbon oil, the hydrocarbon oil is contacted in a fluid catalytic cracking unit with a catalyst system as described above to produce light olefins and gasoline fuel. A detailed description of the cracking process including the catalyst system as an integral component is provided below.

[0059] In certain embodiments of the process, a hydrocarbon oil mixture having a boiling range above 350° C. is provided and the reactor operates at a reaction temperature range of 450° C. to 700° C., a pressure of 1 bar (100 kPa) to 10 bar (1,000 kPa), a residence or contact time of about 0.1 seconds to about 60 seconds, and a catalyst to oil weight ratio of about 2:1 to about 30:1. Fluid catalytic cracking can be operated under conditions effective to maximize the production of gasoline and light olefins and / or under conditions effective to maximize the production of light olefins.

[0060] As used herein, "heavy hydrocarbons" refers to petroleum fractions having a nominal boiling point above 350°C, including common refinery streams such as vacuum gas oil (VGO), unconverted residual oil or recycle oil of a hydrocracking unit, deasphalted oil (DAO) obtained from a solvent deasphalting process, demetallized oil, light or heavy coker gas oil obtained from a coker process, cycle oil obtained from another fluid catalytic cracking process or recycled from an FCC process using the present catalyst, gas oil obtained from a visbreaking process, or combinations comprising at least one of the hydrogenated derivatives of the foregoing sources or oils.

[0061] According to some embodiments, the fluid catalytic cracking unit may include a riser reactor or a downer reactor. As used in this disclosure, the term "downer" refers to a reactor, such as a fluidized bed reactor, in which the reactants flow in a generally downward direction, e.g., entering the top of the reactor and exiting the bottom. Similarly, the term "riser" refers to a reactor, such as a fluidized bed reactor, in which the reactants flow in a generally upward direction, e.g., entering the bottom of the reactor and exiting the top of the reactor.

[0062] A catalyst system suitable for the particular charge and desired products can be delivered to one or more fluid catalytic cracking reactors. In certain embodiments, an FCC catalyst mixture comprising an FCC base catalyst and an FCC catalyst additive is used in the FCC unit to promote the formation of olefins, including but not limited to propylene, and to minimize olefin-consuming reactions, such as hydrogen transfer reactions.

[0063] The fluid catalytic cracking based on the catalyst for fluid catalytic cracking according to the present invention can be carried out under the normal fluid catalytic cracking conditions of hydrocarbon oil. For example, the conditions described below can be suitably used. The above-mentioned catalyst system can be loaded into a reactor and suitably used for catalytic cracking of hydrocarbon oil according to the known FCC process for producing gasoline and / or light olefins including ethylene, propylene, and butylene.

[0064] In fluid catalytic cracking, the hydrocarbon oil may be derived from one or more of crude oil, synthetic crude oil, bitumen, oil sands, shale oil, and coal liquids. These feeds may include petroleum fractions having a standard point above 350°C, including naphtha, diesel, vacuum gas oil (VGO), deasphalted oil (DAO) obtained from a solvent deasphalting process, demetalized oil, light or heavy coker gas oil obtained from a coker process, cycle oil obtained from another fluid catalytic cracking process or recycled from an FCC process using the catalyst, gas oil obtained from a visbreaking process, or a combination comprising at least one of the foregoing.

[0065] For example, a catalytic cracking unit can be loaded with the above-mentioned FCC catalyst and a hydrocarbon oil having a boiling point above 350° C. (in one particular embodiment, from about 350° C. to about 850° C.) and cracked using fluid catalytic cracking at a reaction temperature of about 450° C. to about 700° C., a pressure of 1 bar (100 kPa) to 10 bar (1,000 kPa), a residence time or contact time in the range of about 0.1 seconds to about 60 seconds, and a catalyst to oil weight ratio in the range of about 2:1 to about 30:1.

[0066] In certain embodiments, a fluid catalytic cracking unit with a riser reactor is provided that operates under conditions that promote the formation of light olefins, particularly propylene, and minimize light olefin consuming reactions, including hydrogen transfer reactions. FIG. 1 is a simplified schematic diagram of a riser fluid catalytic cracking unit. The fluid catalytic cracking unit 150 includes a riser reactor. The fluid catalytic cracking unit 150 includes a reactor / separator 160 having a riser section 161, a reaction zone 163, and a separation zone 165. The fluid catalytic cracking unit 150 also includes a regeneration vessel 167 for regenerating spent catalyst. In certain embodiments, a charge 136 is introduced into the reaction zone, along with steam or other suitable gas (not shown) for atomization of the feed. The charge 136 is mixed and intimately contacted with an effective amount of heated fresh or regenerated solid cracking catalyst particles conveyed from the regeneration vessel 167 via conduit 169. The feed mixture and the cracking catalyst are contacted under conditions to form a suspension that is introduced into the riser 161. In a continuous process, a mixture of cracking catalyst and hydrocarbon feedstock passes upward through riser 161 to reaction zone 163. In the riser 161 and reaction zone 163, thermal cracking catalyst particles catalytically crack larger hydrocarbon molecules by cleavage of carbon-carbon bonds.

[0067] During the reaction, as is common in fluid catalytic cracking operations, the cracking catalyst becomes coked and thus access to active catalyst sites is limited or nonexistent. The reaction products are separated from the coked catalyst using any suitable configuration known in fluid catalytic cracking units, for example, generally referred to as separation zone 165 in fluid catalytic cracking unit 150, located at the top of reactor 160 above reaction zone 163. The separation zone may include any suitable device known to those skilled in the art, such as, for example, a cyclone. The reaction products are removed through conduit 171. Catalyst particles including coke deposits from the fluid cracking of the hydrocarbon feed proceed through conduit 173 to regeneration zone 167. In accordance with the process herein, since the light solvent feed is combined with the heavy feed as feed 136, the solvent to oil ratio in the initial solvent deasphalting / demetallization process is selected to provide sufficient coking of the catalyst to provide a heat balance during regeneration.

[0068] In regeneration zone 167, the coked catalyst is contacted with a stream of oxygen-containing gas, such as pure oxygen or air, which enters regeneration zone 167 via conduit 175. Regeneration zone 167 operates under configurations and conditions known in typical fluid catalytic cracking operations. For example, regeneration zone 167 may be operated as a fluidized bed producing a regeneration off-gas including combustion products that is discharged through conduit 177. The hot regenerated catalyst is transported from regeneration zone 167 through conduit 169 to the bottom of riser 161 for mixing with the hydrocarbon feed, as described above.

[0069] Generally, operating conditions for a suitable riser fluid catalytic cracking unit reactor using the catalysts herein include the following: a reaction temperature of about 480° C. to about 650° C., in certain embodiments about 500° C. to about 620° C., and in further embodiments about 500° C. to about 600° C.; 2 from about 20kg / cm 2 and in one particular embodiment, about 1 kg / cm 2 from about 10kg / cm 2 and in a further embodiment about 1 kg / cm 2 from about 3kg / cm2 a reaction pressure of from about 0.5 seconds to about 10 seconds, and in certain embodiments from about 1 second to about 5 seconds, and in further embodiments from about 1 second to about 2 seconds contact time (in the reactor); and a catalyst to feed ratio of from about 1:1 to about 15:1, and in certain embodiments from about 1:1 to about 10:1, and in further embodiments from about 8:1 to about 20:1.

[0070] In certain embodiments, a fluid catalytic cracking unit with a downflow reactor is provided that operates under conditions that promote the formation of light olefins, particularly propylene, and minimize light olefin-consuming reactions, including hydrogen transfer reactions. FIG. 2 is a simplified schematic diagram of a downflow fluid catalytic cracking unit. The fluid catalytic cracking unit 250 includes a reactor / separator 260 having a reaction zone 262 and a separation zone 264. The fluid catalytic cracking unit 250 also includes a regeneration zone 266 for regenerating spent catalyst. In particular, in certain embodiments, a charge 236 is introduced into the reaction zone, along with steam or other suitable gas (not shown) for atomization of the feed. An effective amount of heated fresh or hot regenerated solid cracking catalyst particles from the regeneration zone 266 is conveyed to the top of the reaction zone 262 and transferred, for example, via a downward conduit or pipe 268, commonly referred to as a transfer line or standpipe, to a collection well or hopper (not shown) at the top of the reaction zone 262. The hot catalyst flow is typically stabilized so that it is uniformly directed into the mixing zone or feed injection portion of the reaction zone 262. The charge 236 is typically injected into the mixing zone through feed injection nozzles located near the point of introduction of the regenerated catalyst into the reaction zone 262. These multiple injection nozzles provide thorough and uniform mixing of the catalyst and oil. When the charge contacts the hot catalyst, the cracking reaction occurs.

[0071] The hydrocarbon cracked products, unreacted feed, and reaction vapors of the catalyst mixture flow rapidly through the remainder of the reaction zone 262 and enter a rapid separation zone 264 at the bottom of the reactor / separator 260. The cracked and uncracked hydrocarbons are directed through a conduit or pipe 270 to a conventional product recovery section known in the art to produce fluid catalytic cracking products light olefins, gasoline, and cycle oil with maximized propylene yields. If temperature control is required, a quench injection can be provided near the bottom of the reaction zone 262 just before the separation zone 264. This quench injection can be utilized to rapidly reduce or stop the cracking reaction and control the severity of the cracking.

[0072] The reaction temperature, i.e., the outlet temperature of the downflow reactor, can be controlled by opening and closing a catalyst slide valve (not shown) that controls the flow of regenerated catalyst from the regeneration zone 266 to the top of the reaction zone 262. The heat required for the endothermic cracking reaction is provided by the regenerated catalyst. By varying the flow rate of the thermally regenerated catalyst, the severity of operation or cracking conditions can be controlled to produce a desired product slate. A stripper 272 is also provided to separate the oil from the catalyst that is transferred to the regeneration zone 266. The catalyst from the separation zone 264 flows to a lower section of the stripper 272 that includes a catalyst section, where a suitable stripping gas, such as steam, is introduced via streamline 274. The stripping section typically includes several baffle structured packings (not shown) over which the downwardly flowing catalyst 280 passes countercurrent to the flowing stripping gas. The upwardly flowing stripping gas, typically steam, is used to "strip" or remove any additional hydrocarbons remaining within the catalyst pores or between the catalyst particles. The stripped or spent catalyst is carried through a lift riser in the regeneration zone 266 by lift from the combustion air stream 276. This spent catalyst, which may also be contacted with additional combustion air, provides controlled combustion of accumulated coke. Flue gas is removed from the regenerator via conduit 278. In the regenerator, heat generated from the combustion of by-product coke is transferred to the catalyst to raise the temperature necessary to provide heat for the endothermic cracking reaction in the reaction zone 262. In accordance with the process herein, since the light solvent feed is combined with the heavy feed as feed 236, the solvent to oil ratio in the initial solvent deasphalting / demetallization process is selected to provide sufficient coking of the catalyst to provide a heat balance during regeneration.

[0073] Important characteristics of a downflow reactor include introduction of the feedstock by downward flow at the top of the reactor, shorter residence time compared to a riser reactor, and a high catalyst to oil ratio, for example in the range of about 20:1 to about 30:1. In general, suitable propylene producing downflow FCC unit reactor operating conditions include the following: reaction temperature of 550°C to 650°C, in certain embodiments 580°C to 630°C, and in further embodiments 590°C to 620°C; 2 from 20kg / cm 2 and in one particular embodiment, 1 kg / cm 2 from 10kg / cm 2 and in a further embodiment about 1 kg / cm 2 from about 3kg / cm 2 a reaction pressure of from 0.1 seconds to 30 seconds, and in certain embodiments from 0.1 seconds to 10 seconds, and in further embodiments from 0.2 seconds to 0.7 seconds (in the reactor); and a catalyst to feed ratio of from 1:1 to 40:1, and in certain embodiments from 1:1 to 30:1, and in further embodiments from 10:1 to 30:1.

[0074] For clarity, in the foregoing description of an FCC unit, the numerous valves, temperature sensors, electronic process controllers, and other equipment conventionally used and familiar to those skilled in the art of solvent deasphalting / demetallization and fluid catalytic cracking have not been included in the accompanying schematic diagram. Not shown are ancillary systems utilized in conventional fluid catalytic cracking systems, such as air supply, catalyst hopper, torch oil supply, flue gas treatment and heat recovery, fresh and spent catalyst hoppers for storage of make-up and spent / equilibrium catalyst that can be added to or removed from the regenerator. EXAMPLES

[0075] The embodiments described in this disclosure will be better understood by reference to the following examples, which are provided by way of illustration and are not meant to be limiting, as one of ordinary skill in the art will recognize.

[0076] The unconverted hydrocracked residual oil stream, the properties and composition of which are shown in Table 1, was catalytically cracked in a MAT (Micro Activity Test) unit under identical conditions of 550°C, 30 seconds residence time, and 4:1 catalyst to oil ratio using three different catalyst systems as a basis for comparison. For Example 1 (comparison), the catalyst system included a (Ti,Zr)-USY zeolite catalyst but no catalyst additive. For Example 2, the catalyst system included a (Ti,Zr)-USY zeolite catalyst as the only zeolite catalyst without additional additives. * As Example 3, the catalyst system was the (Ti,Zr)-USY zeolite catalyst of Example 1 and the (Ti,Zr)- * It is a mixture of BEA zeolite and (Ti,Zr)-USY. * The weight ratio to BEA was 9: 1. The results of three experiments are presented in Table 2.

[0077] [Table 1]

[0078] [Table 2]

[0079] Example 1 demonstrated the performance of a typical FCC catalyst optimized for maximum propylene yield. The propylene yield from only the (Ti,Zr)-USY zeolite catalyst was 2.65 wt%. Example 2 demonstrated the performance of a typical FCC catalyst optimized for maximum propylene yield from only the (Ti,Zr)-USY zeolite catalyst according to an embodiment of the present disclosure as the sole catalytic zeolite. * The performance of BEA zeolite was demonstrated. (Ti,Zr)- * The propylene yield of the BEA zeolite was 2.56 wt%, which was almost the same as that of the conventional (Ti,Zr)-USY zeolite catalyst. *This demonstrates a synergistic combination with BEA zeolite, showing a four-fold increase in propylene yield to 11 wt%. Thus, the (Ti,Zr)- * In addition to being acceptable catalysts by themselves, the BEA zeolites are believed to provide particularly favorable propylene yields when included in conventional FCC catalysts.

[0080] Item List Embodiments of the present disclosure include at least the following items, which are not intended to limit the scope of the entire disclosure or the appended claims.

[0081] Item 1: A method for cracking a hydrocarbon oil, comprising contacting the hydrocarbon oil with a catalyst system in a fluid catalytic cracking unit to produce light olefins and gasoline fuel, wherein the catalyst system comprises an FCC-based catalyst and a catalyst additive; the FCC-based catalyst comprises a Y-zeolite; and the catalyst additive comprises a framework-substituted * Contains BEA type zeolites; and framework-substituted * BEA-type zeolite was modified * The modified BEA scaffold * The BEA skeleton is * The BEA aluminosilicate framework has been modified by replacing a portion of the framework aluminum atoms with beta zeolite Al-replacement atoms independently selected from the group consisting of titanium atoms, zirconium atoms, and hafnium atoms. * The method includes the BEA aluminosilicate framework.

[0082] Item 2: Backbone-replaced * BEA-type zeolites are those which have been substituted with the framework. * 2. The method according to claim 1, wherein the beta zeolite contains from 0.01% to 5% Al-substituted atoms, calculated on an oxide basis, based on the total mass of the BEA type zeolite.

[0083] Item 3: Backbone-replaced * BEA-type zeolites are those which have been substituted with the framework. *The method according to claim 1 or 2, comprising: 0.01% to 5% by weight of substitution atoms, calculated on an oxide basis, based on the total weight of the BEA type zeolite; and the beta zeolite Al substitution atoms comprise a combination selected from the group consisting of: (a) titanium atoms and zirconium atoms, (b) titanium atoms and hafnium atoms, (c) zirconium atoms and hafnium atoms, and (d) titanium atoms, zirconium atoms, and hafnium atoms.

[0084] Item 4: Backbone-substituted * BEA-type zeolites are those which have been substituted with the framework. * 4. The method according to any one of items 1 to 3, wherein the beta zeolite contains 0.01% to 5% Al-substituted atoms, calculated on an oxide basis, based on the total mass of the BEA type zeolite; and the beta zeolite Al-substituted atoms contain titanium atoms and zirconium atoms.

[0085] Item 5: Backbone-substituted * BEA-type zeolite is (a) 400m 2 / g to 800m 2 / g; (b) SiO2 to Al2O3 molar ratio from 10 to 200; (c) 0.2 cm 3 / g to 0.6cm 3 / g pore volume; and (d) crystal lattice constants a = 1.260 nm to 1.270 nm, b = 1.260 nm to 1.270 nm, and c = 2.620 to 2.650 nm.

[0086] Item 6: The method according to any one of items 1 to 5, wherein the weight ratio of the FCC-based catalyst to the catalyst additive in the catalyst system is from 2:1 to 1,000:1, based on the combined weight of the FCC-based catalyst and the catalyst additive.

[0087] Item 7: The method according to any one of items 1 to 6, wherein the weight ratio of the FCC-based catalyst to the catalyst additive in the catalyst system is from 4:1 to 100:1, based on the combined weight of the FCC-based catalyst and the catalyst additive.

[0088] Item 8. The method of any one of items 1 to 7, wherein the weight ratio of FCC-based catalyst to catalyst additive in the catalyst system is from 6:1 to 20:1, based on the combined weight of the FCC-based catalyst and catalyst additive.

[0089] Item 9: The method of any one of items 1 to 8, wherein the catalyst system comprises an FCC-based catalyst, a catalyst additive, a catalyst matrix support, a binder, and a filler.

[0090] Item 10: The method of item 9, wherein the catalyst matrix support comprises alumina or silica-alumina; the binder is a sol of a porous inorganic oxide selected from the group consisting of alumina, silica, boria, chromia, magnesia, zirconia, titania, silica-alumina, and combinations thereof; and the filler is a clay selected from the group consisting of kaolin, montmorillonite, halloysite, bentonite, and combinations thereof.

[0091] Item 11: The method according to item 9 or 10, wherein the catalyst system comprises, based on the total weight of the catalyst system, 1 wt.% to 50 wt.% of an FCC-based catalyst; 1 wt.% to 50 wt.% of a catalyst additive; 0.1 wt.% to 15 wt.% of a binder; and 0.1 wt.% to 15 wt.% of a clay.

[0092] Item 12: The method according to any one of items 1 to 11, wherein the weight ratio of the FCC-based catalyst to the catalyst additive in the catalyst system is from 6:1 to 20:1, based on the combined weight of the FCC-based catalyst and the catalyst additive.

[0093] Item 13: Backbone-substituted * 13. The method according to any of items 1 to 12, wherein the BEA type zeolite has mesopores with a diameter of 2 nm to 100 nm.

[0094] Item 14: The method of any one of items 1 to 13, wherein the Y-zeolite comprises an ultrastable Y-zeolite or a framework-substituted ultrastable Y-zeolite.

[0095] Item 15: The method according to any one of items 1 to 14, wherein the FCC-based catalyst comprises a framework-substituted ultrastable Y (USY)-zeolite; and the framework-substituted USY-zeolite has a modified USY framework, the modified USY framework comprising a USY aluminosilicate framework modified by replacing a portion of the framework aluminum atoms of the USY aluminosilicate framework with USY-zeolite Al-substituting atoms independently selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof.

[0096] Item 16: The method according to item 14 or 15, wherein the framework-substituted ultrastable Y-zeolite contains 0.01% to 5% USY-zeolite Al-substituted atoms, calculated on an oxide basis, based on the total mass of the framework-substituted ultrastable Y-zeolite.

[0097] Item 17: A framework-substituted ultrastable Y-type zeolite with crystal lattice constants a and b of (a) 2.430 nm to 2.460 nm; (b) 600 nm 2 / g to 900m 2 / g; and (c) a molar ratio of SiO2 to Al2O3 of 5:1 to about 100:1.

[0098] Item 18: Backbone replaced * BEA-type zeolites are those which have been substituted with the framework. * 18. The method according to any of items 14 to 17, wherein the beta zeolite contains 0.01% to 5% Al-substituted atoms, calculated on an oxide basis, based on the total mass of the BEA-type zeolite; the beta zeolite Al-substituted atoms contain titanium and zirconium atoms; the framework-substituted ultrastable Y-zeolite contains 0.01% to 5% USY-zeolite Al-substituted atoms, calculated on an oxide basis, based on the total mass of the framework-substituted ultrastable Y-zeolite; and the USY-zeolite Al-substituted atoms contain titanium and zirconium atoms.

[0099] Item 19: The method according to any of items 1 to 18, wherein the hydrocarbon oil comprises a hydrocarbon component having a boiling range greater than 350°C; and the contacting is carried out at a reaction temperature of 450°C to 700°C, a reaction pressure of 1 bar (100 kPa) to 10 bar (1,000 kPa), a residence time or contact time of 0.1 seconds to 60 seconds, and a catalyst to oil ratio of about 2:1 to 30:1.

[0100] Item 20: The method according to any one of items 1 to 19, wherein the fluid catalytic cracking unit comprises a riser reactor or a downer reactor.

[0101] Item 21: A framework-substituted beta type zeolite catalyst additive is (a) 400m 2 / g to 800m 2 (b) a molar ratio of SiO2 to Al2O3 of 10 to 200; and (c) a (Ti,Zr)- with crystal lattice constants of a = 1.26 nm to 1.27 nm, b = 1.26 nm to 1.27 nm, and c = 2.62 nm to 2.65 nm. * 21. The method according to any one of items 1 to 20, wherein the zeolite is a BEA zeolite.

[0102] Item 22: Backbone replaced * The BEA type zeolite catalyst additive was (a) 400 m 2 / g to 800m 2 / g; (b) SiO2 to Al2O3 molar ratio of 50 to 60; (c) 0.38 cm 3 / g to 0.43cm 3 / g; and (d) a (Ti,Zr)- with crystal lattice constants of a = 1.26 nm to 1.27 nm, b = 1.26 nm to 1.27 nm, and c = 2.62 nm to 2.65 nm. * 21. The method according to any one of items 1 to 20, wherein the zeolite is a BEA zeolite.

[0103] Item 23: The method of any one of items 1 to 22, wherein the catalyst system further comprises an active metal component comprising iron, cobalt, nickel, rhodium, palladium, silver, iridium, platinum, gold, chromium, molybdenum, or tungsten.

[0104] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this invention belongs. The terms used in the description of this specification are for describing specific embodiments only and are not intended to be limiting. As used in this specification and the appended claims, the singular forms "a", "an" and "the" are intended to include the plural forms unless the context clearly indicates otherwise.

[0105] For purposes of describing and defining this disclosure, it is noted that the term "about" is utilized herein to represent the inherent degree of uncertainty that may result from any quantitative comparison, value, measurement, or other representation. The term "about" is also utilized herein to represent the degree to which a quantitative representation may vary from the cited reference without causing a change in the basic functionality of the subject matter at issue.

[0106] It should be noted that one or more of the following claims utilizes the term "herein" as a transitional phrase. It should be noted that for purposes of defining the present technology, this term is introduced into the claims as an open-ended transitional phrase used to introduce a description of a set of features of a structure, and should be interpreted in the same manner as the more commonly used open-ended preamble term "comprising."

[0107] It is to be understood that any two quantitative values ​​assigned to a property may constitute a range for that property, and all combinations of ranges formed from all recited quantitative values ​​for a given property are contemplated herein.

[0108] While particular embodiments have been illustrated and described herein, it should be understood that various other changes and modifications can be made without departing from the scope of the claimed subject matter. Moreover, although various aspects of the claimed subject matter have been described herein, such aspects need not be utilized in combination. It is therefore intended that the appended claims cover all such changes and modifications that are within the scope of the claimed subject matter. Preferred embodiments of the present invention will be described below in detail. EMBODIMENT 1 1. A method for cracking a hydrocarbon oil, comprising: contacting said hydrocarbon oil with a catalyst system in a fluid catalytic cracking unit to produce light olefins and gasoline fuel. where the catalyst system comprises an FCC-based catalyst and a catalyst additive; the FCC-based catalyst comprises Y-zeolite; The catalyst additive is a backbone-substituted * Contains a zeolite of the BEA type, and The backbone substituted * BEA-type zeolite was modified * The modified BEA scaffold * The BEA skeleton is * Modified by replacing a portion of the framework aluminum atoms of the BEA aluminosilicate framework with beta zeolite Al-substituting atoms selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof. * Contains a BEA aluminosilicate framework method. EMBODIMENT 2 The backbone substituted * BEA-type zeolites are those which have been substituted with the framework. * 2. The method of embodiment 1, wherein the beta zeolite contains 0.01% to 5% Al-substituted atoms, calculated on an oxide basis, based on the total mass of the BEA type zeolite. EMBODIMENT 3 The backbone substituted * BEA-type zeolites are those which have been substituted with the framework. * Contains from 0.01% to 5% by weight of substitution atoms, calculated on an oxide basis, based on the total weight of the BEA type zeolite; and The beta zeolite Al-substituted atoms include combinations selected from the group consisting of: (a) titanium atoms and zirconium atoms, (b) titanium atoms and hafnium atoms, (c) zirconium atoms and hafnium atoms, and (d) titanium atoms, zirconium atoms, and hafnium atoms; 3. The method according to embodiment 1 or 2. EMBODIMENT 4 The backbone substituted * BEA-type zeolites are those which have been substituted with the framework. * containing 0.01% to 5% beta zeolite Al-substituted atoms, calculated on an oxide basis, based on the total mass of the BEA type zeolite; and The beta zeolite Al-substituted atoms include titanium and zirconium atoms; 4. The method according to any one of claims 1 to 3. EMBODIMENT 5 The backbone substituted * BEA type zeolite is (a) 400m 2 / g to 800m 2 / g specific surface area, (b) SiO from 10 to 200 2 Al 2 O 3 Molar ratio to (c) 0.2 cm 3 / g to 0.6cm 3 / g pore volume, and (d) Crystal lattice constants a = 1.260 nm to 1.270 nm, b = 1.260 nm to 1.270 nm, and c = 2.620 to 2.650 nm 5. The method according to any one of claims 1 to 4, comprising the steps of: EMBODIMENT 6 6. The method of any one of the preceding claims, wherein the weight ratio of the FCC-based catalyst to the catalytic additive in the catalyst system is from 2:1 to 1,000:1, based on the combined weight of the FCC-based catalyst and the catalytic additive. EMBODIMENT 7 7. The method of any one of the preceding claims, wherein the catalyst system comprises the FCC-based catalyst, the catalyst additive, a catalyst matrix support, a binder, and a filler. EMBODIMENT 8 the catalytic matrix support comprises alumina or silica-alumina; the binder is a sol of a porous inorganic oxide selected from the group consisting of alumina, silica, boria, chromia, magnesia, zirconia, titania, silica-alumina, and combinations thereof; and The filler is a clay selected from the group consisting of kaolin, montmorillonite, halloysite, bentonite, and combinations thereof. 8. The method of embodiment 7. EMBODIMENT 9 The catalyst system comprises, based on the total weight of the catalyst system: 1 wt. % to 50 wt. % of an FCC-based catalyst; 1% to 50% by weight of a catalytic additive; 0.1% to 15% by weight of a binder, and 0.1% to 15% clay by weight 9. The method of embodiment 7 or 8, comprising: EMBODIMENT 10 10. The method of any one of the preceding claims, wherein the weight ratio of the FCC-based catalyst to the catalytic additive in the catalyst system is from 6:1 to 20:1, based on the combined weight of the FCC-based catalyst and the catalytic additive. EMBODIMENT 11 The FCC-based catalyst comprises a framework-substituted ultrastable Y (USY)-zeolite; and The framework-substituted USY-zeolite has a modified USY framework, the modified USY framework comprising a USY aluminosilicate framework modified by replacing a portion of the framework aluminum atoms of the USY aluminosilicate framework with USY-zeolite Al-substituting atoms selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof. 2. The method of embodiment 1. EMBODIMENT 12 12. The method of embodiment 11, wherein the framework-substituted ultrastable Y-zeolite comprises 0.01% to 5% USY-zeolite Al-substituted atoms, calculated on an oxide basis, based on the total mass of the framework-substituted ultrastable Y-zeolite. EMBODIMENT 13 The framework-substituted ultrastable Y-type zeolite is (a) Crystal lattice constants a and b from 2.430 nm to 2.460 nm; (b) 600m 2 / g to 900m 2 / g specific surface area, and (c) SiO:5:1 to about 100:1 2 Al 2 O 3 Molar ratio of to 13. The method of embodiment 11 or 12, comprising: EMBODIMENT 14 The backbone substituted * BEA-type zeolites are those which have been substituted with the framework. * containing 0.01% to 5% beta zeolite Al-substituted atoms, calculated on an oxide basis, based on the total mass of the BEA type zeolite; The beta zeolite Al-substituted atoms include titanium and zirconium atoms; the framework-substituted ultrastable Y-zeolite contains from 0.01% to 5% USY-zeolite Al-substituting atoms, calculated on an oxide basis, based on the total weight of the framework-substituted ultrastable Y-zeolite; and The USY-zeolite Al-substituted atoms include titanium and zirconium atoms; 14. The method according to any one of embodiments 11 to 13. EMBODIMENT 15 The hydrocarbon oil comprises a hydrocarbon component having a boiling range greater than 350° C.; and the contacting is carried out at a reaction temperature of from 450° C. to 700° C., a reaction pressure of from 1 bar (100 kPa) to 10 bar (1,000 kPa), a residence or contact time of from 0.1 seconds to 60 seconds, and a catalyst to oil ratio of from about 2:1 to 30:1; 15. The method according to any one of embodiments 1 to 14. [Explanation of symbols]

[0109] 136 Raw materials / filling 150 Fluid Catalytic Cracking Unit 160 Reactor 161 Liza 163 Reaction Zone 165 Separation Zone 167 Regeneration Zone 169,171,173,175,177 conduit 236 Raw materials 250 Fluid Catalytic Cracking Unit 260 Reactor / Separator 262 Reaction Zone 264 Separation Zone 266 Regeneration Zone 268 Downward conduit or pipe 270 Conduits or pipes 272 Stripper 274 Streamline 276 Combustion Air Flow 278 Conduit 280 Catalyst

Claims

1. 1. A method for cracking a hydrocarbon oil, comprising: contacting said hydrocarbon oil with a catalyst system in a fluid catalytic cracking unit to produce light olefins and gasoline fuel. where the catalyst system comprises an FCC-based catalyst and a catalyst additive; the FCC-based catalyst comprises a framework-substituted ultrastable Y (USY)-zeolite containing 0.01% to 5% USY-zeolite Al-substituting atoms, calculated on an oxide basis, based on the total mass of the framework-substituted ultrastable Y-zeolite; the framework-substituted USY-zeolite has a modified USY framework, the modified USY framework comprising a USY aluminosilicate framework modified by replacing a portion of the framework aluminum atoms of the USY aluminosilicate framework with USY-zeolite Al-substituting atoms selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof; The catalyst additive is a backbone-substituted * A zeolite of the BEA type, wherein the framework substituted * Based on the total mass of the BEA type zeolite, calculated on an oxide basis, the framework substituted beta zeolite contains 0.01% to 5% Al-substituted atoms. * Contains BEA type zeolite, and The backbone substituted * BEA type zeolite was modified * The modified BEA scaffold * The BEA skeleton is * Modified by replacing a portion of the framework aluminum atoms of the BEA aluminosilicate framework with beta zeolite Al-substituting atoms selected from the group consisting of titanium atoms, zirconium atoms, hafnium atoms, and combinations thereof; * comprising a BEA aluminosilicate framework, the weight ratio of the FCC-based catalyst to the catalytic additive in the catalyst system is 9:1, based on the combined weight of the FCC-based catalyst and the catalytic additive; method.

2. The beta zeolite Al-substituted atoms include combinations selected from the group consisting of: (a) titanium and zirconium atoms, (b) titanium and hafnium atoms, (c) zirconium and hafnium atoms, and (d) titanium, zirconium, and hafnium atoms. The method of claim 1.

3. The beta zeolite Al-substituted atoms include titanium and zirconium atoms; The method of claim 1.

4. The backbone substituted * BEA type zeolite is (a) 400m 2 / g to 800m 2 / g specific surface area, (b) 10 to 200 SiO 2 Al 2 O 3 Molar ratio to (c) 0.2 cm 3 / g to 0.6 cm 3 / g pore volume, and (d) Crystal lattice constants a = 1.260 nm to 1.270 nm, b = 1.260 nm to 1.270 nm, and c = 2.620 to 2.650 nm 2. The method of claim 1, comprising:

5. The method of claim 1 , wherein the catalyst system comprises the FCC-based catalyst, the catalyst additive, a catalyst matrix support, a binder, and a filler.

6. the catalytic matrix support comprises alumina or silica-alumina; the binder is a sol of a porous inorganic oxide selected from the group consisting of alumina, silica, boria, chromia, magnesia, zirconia, titania, silica-alumina, and combinations thereof; and The filler is a clay selected from the group consisting of kaolin, montmorillonite, halloysite, bentonite, and combinations thereof. The method according to claim 5.

7. The framework-substituted ultrastable Y-type zeolite is (a) crystal lattice constants a and b between 2.430 nm and 2.460 nm; (b) 600m 2 / g to 900m 2 / g specific surface area, and (c) SiO from 5:1 to 100:1 2 Al 2 O 3 Molar ratio to 2. The method of claim 1, comprising:

8. The beta zeolite Al-substituted atoms include titanium and zirconium atoms; and The USY-zeolite Al-substituted atoms include titanium and zirconium atoms; The method of claim 1.

9. The hydrocarbon oil comprises a hydrocarbon component having a boiling range greater than 350° C.; and said contacting being carried out at a reaction temperature of from 450° C. to 700° C., a reaction pressure of from 1 bar (100 kPa) to 10 bar (1,000 kPa), a residence or contact time of from 0.1 seconds to 60 seconds, and a catalyst to oil ratio of from 2:1 to 30:1; The method of claim 1.

Citation Information

Patent Citations

  • Zirconium-containing beta zeolite and preparation method thereof

    CN104549453A

  • JP1978159492U

  • zeolite beta hydrocarbon conversion catalyst production

    JP1991505839A

  • molecular sieve cit-6

    JP2002519281A

  • Cracking catalyst and method for producing the same

    JP2008508084A